Threshold Voltage Shift of Flexible P-Type Poly-Silicon Thin Film Transistors Under Illumination Stress - Weipeng Ji; Huaisheng Wang; Mingxiang Wang; Dongli Zhang; Nannan Lv; Qi Shan (IEEE Journal of the Electron Devices Society)
The reliability of flexible p-type low temperature poly-silicon thin film transistors (TFTs) under sole illumination stress was investigated. As the TFT was exposed to illumination, the transfer characteristic curves of the TFTs shifted positively, accompanied by an increase in the off-state current. Through altering the wavelength and intensity of the light, the degradation mechanism for TFTs under illumination stresses can be attributed to photoexcited carriers and residual hydrogen diffusion from the Si3N4 layer to air, leading to a forward shift in the threshold voltage. Moreover, TFTs exposed to the air for an extended period can also effectively remove residual hydrogen in the silicon nitride layer, thereby effectively suppressing photoinduced degradation of the device and improving its reliability.